Iowa Birdline update, November 21, 1994 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1994)
Email of the Iowa Birdline update for November 21, 1994. Highlights of the update include sightings of a Little Gull, a Black-headed Gull, numerous Tundra Swans Also of note was a report of an estimated 200,000 waterfowl, mostly Canvasbacks and Lesser Scaups. Also included are handwritten notes for the next week's update with sightings of a Northern Shrike, a Snowy Owl, and several species of Grebes. Epson - sheet feed/flatbed